Eating behaviors and physical activity during the COVID-19 pandemic lockdown: experiences of breast cancer patients on adjuvant hormonal therapy - Paunović, Marija; Ristić-Medić, Danijela; Arsić, Aleksandra; Petrović, Snježana; Krstić, Predrag; Kojadinović, Milica; Vučić, Vesna (Vojnosanitetski pregled, 2024)
Background/Aim. Since the coronavirus disease 2019 (COVID-19) pandemic led to a strict lockdown in Serbia, the population has experienced drastic lifestyle changes. Physical distancing, self-isolation, limited availability of essential food products, and the stress related to the availability of therapy during the pandemic particularly affected the lives of vulnerable groups, such as breast cancer (BrC) patients. The aim of this study was to examine the changes in eating behaviors and physical activity of postmenopausal BrC patients on adjuvant hormonal therapy under the COVID-19 lockdown conditions. Methods. This observational retrospective pre-post cohort study included 32 women treated with aromatase inhibitors (AIs) who responded to telephone interviews using a structured questionnaire. The questionnaire aims to collect data on eating habits (intake of certain foods on a daily/weekly basis, as well as changes in the usual choice of food), intake of supplements, changes in weight, and physical activity before and during the lockdown. Results. The results showed that, due to problems in obtaining groceries, the patients cooked and consumed homemade sweets and fruit more often (47% of the respondents), while fewer (31%) consumed fresh fish. Nearly 41% of patients reported increased food intake, and 88% reported decreased physical activity, which led to an increase in body weight in as many as 47% of subjects. The intake of supplements was doubled. Conclusion. The COVID-19 lockdown with home confinement exacerbated health risks and affected dietary patterns and physical activity, which may have had a negative impact on the long-term health of BrC patients treated with AIs.
Keywords: COVID-19 lockdown; eating behaviours; nutritional survey; breast cancer; aromatase inhibitors